Financial Decision-Making: Are Women Really More Risk Averse? - Schubert, Renate; Brown, Martin; Gysler, Matthias; Brachinger, Hans Wolfgang (American Economic Review, 1999)
Financial Decision-Making: Are Women Really More Risk-Averse? by Renate Schubert, Martin Brown, Matthias Gysler and Hans Wolfgang Brachinger. Published in volume 89, issue 2, pages 381-385 of American Economic Review, May 1999